EDUKASI DAN PROMOSI KESEHATAN: PENGGUNAAN OBAT HERBAL YANG AMAN DAN EFEKTIF BAGI MASYARAKAT KECAMATAN PADANG UTARA KOTA PADANG - Dwisari Dillasamola; Hansen Nasif; Yohannes Alen; Almahdy Almahdy; Airiza Fitri Andini; Syawwal Al-Khansaa (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
Herbal medicine is an alternative treatment made from natural materials such as plants, animals, or minerals and is often used by the community in addition to modern medicine. The use of traditional medicine in Indonesia is still believed by some people to treat various diseases. Herbal medicine has become an important part of traditional medicine in various parts of the world. Despite its potential, public knowledge regarding the safe and effective use of herbal medicines is still relatively low. For this reason, health promotion and education activities were carried out in the community to increase public understanding and knowledge about the use and benefits of herbal medicines. This activity was attended by 27 participants, mainly from mothers around the implementation location. Prior to the education, a questionnaire survey was conducted, which showed that 51.80% of the respondents had basic knowledge about herbal medicines. The enthusiasm of the participants was very high during the presentation of the material, indicating a great interest in understanding herbal medicine more deeply. The results of this activity showed a significant increase in knowledge among participants regarding the use of herbal medicine, especially in choosing cough medicines safely and effectively. It is hoped that this activity will not only have a positive impact on improving public health, but also equip them with a better understanding of using herbal medicines wisely and appropriately. With the high interest of the community in participating in this activity, it is concluded that this activity has a very positive impact on the community and fosters knowledge and awareness of the community to live a healthy life.